2020
DOI: 10.1016/j.morpho.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Triceps, quadriceps or pentaceps femoris? Need for proper muscle definition

Abstract: Introduction: Over the last years, the definition of quadriceps femoris (QF) has evolved somewhat and some authors now define a fifth head: the tensor of vastus intermedius (TVI).Descriptions of the different components of QF in textbooks and recent findings remain confusing. Therefore, the aim of this study is to obtain more information on this possible fifth head.Materials and methods: Twenty lower limbs of 10 embalmed cadavers, six females and four males, were investigated by macro-dissection. The dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Veeramani et al confirmed this classification in their study of 36 limbs of the South Indian population (Veeramani & Gnanasekaran, 2017); however, the tendons did not show as much diversity. In contrast, Bonnechère et al (2020)'s study identified the TVI in only seven of 20 limbs studied, and in four cases, it was not possible to differentiate the VI and VM or the VI and VL.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Veeramani et al confirmed this classification in their study of 36 limbs of the South Indian population (Veeramani & Gnanasekaran, 2017); however, the tendons did not show as much diversity. In contrast, Bonnechère et al (2020)'s study identified the TVI in only seven of 20 limbs studied, and in four cases, it was not possible to differentiate the VI and VM or the VI and VL.…”
Section: Discussionmentioning
confidence: 76%
“…The fifth head's incidence has been found to range from 29 to 100% (Bonnechère et al, 2020; Grob, Ackland, et al, 2016; Veeramani & Gnanasekaran, 2017; Willan et al, 1990). Golland and Mahon (1986) reported the presence of a separate muscle belly of the VL in 29% of dissected limbs, while Willian et al (1990) observed an additional muscle between the VL and VI in 36% of cases, and Bonnechère et al (2020) noted the TVI's presence in 35% of limbs. In contrast, both Grob, Ackland, et al (2016) and Veeramani and Gnanasekaran (2017)) reported that the TVI was present in all limbs examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly however, a recent study investigating the tensor vastus intermedius found conflicting results when compared to the above. The study demonstrated the muscle in only seven of the twenty lower limbs studied [3], and the authors called into question the definition of this muscle. Perhaps, therefore, clarity is needed regarding the muscle's definition in order to allow for objective and comparable research to be undertaken.…”
Section: Morphologymentioning
confidence: 99%